Training on WhatsApp Business Optimization for Student Entrepreneurs of Universitas Syiah Kuala - Rivani, Rivani; Halim, Hendra; Fadhil, Rahmat; Ramadhani, Evi; Agustina, Raida; Purnami, Ni Made; Dinaroe, Dinaroe; Hanidah, In In; Maulana, M. Rizki; Saleha, Sitti (Universitas Syiah Kuala, 2024)
This community service activity aimed to enhance the digital marketing skills of student entrepreneurs at Universitas Syiah Kuala by optimizing the use of WhatsApp Business. Many young entrepreneurs lack familiarity with digital tools that can streamline business operations and expand market reach. This training was designed to address this gap by introducing participants to the practical features of WhatsApp Business. Utilizing the Service Learning (SL) method, the activity included presentations, hands-on practice, and evaluations. The training covered key WhatsApp Business features such as profile setup, product catalog management, and customer messaging. Results showed a marked increase in participants' understanding, with 85% reporting improved competence in using the app for business purposes and 90% expressing greater confidence in leveraging digital marketing tools. This activity highlights the potential of simple, accessible digital tools in supporting young entrepreneurs and contributes to the achievement of Sustainable Development Goals, particularly in promoting economic growth and digital literacy.